The mediating effect of communication between ERM practices and firm performance of SMEs in Malaysia - Khairul Afzan Aziz
Small and Medium Enterprises (SMEs) represent 98.5% of total business in Malaysia and play crucial roles in employment creation, income generation, and improve the socio-economy of the bottom 40% household income group (B40). In Malaysia SMEs' involvement in business expose themselves to risks. Hence, SMEs need risk management as an innovative management approach. Literature reviews showed that the practices of ERM contribute to large firm performance. Although ERM is known as a tool to increase stakeholder's value, few firms have used this new tool to manage risks. The objectives of this research are to identify important factors that encourage the likelihood of ERM practices among non-ERM firms and identify important factors that influence the penetration level of ERM practices among ERM firms. This study also examines whether communication mediates the effect between the penetration level of ERM practices and the firm's performance and evaluates whether the practices ofERM affect the firm's performance of SMEs. Based on the technological-organizational environmental context (TOE) framework and Diffusion of Innovation (001) Theory, the research conceptual framework was formed from four factors, namely, decision maker (D), technology (T), organization (0), and environment (E) as independent variables 1 (IV 1) and the ERM practices as the dependent variable 1 (DV 1). Meanwhile, communication was used as a mediator (M) between the penetration level of ERM practices as independent variable 2 (IV2) and the firm's performance as dependent variables 2 (DV2). Using proportionate stratified random sampling, 300 questionnaires were distributed using a self-administered survey together with 683 online surveys. However, only 192 samples (99 ERM firms, 93 non-ERM firms) were accepted and analyzed using Statistical Package for the Social Sciences (SPSS) and Partial Least Square-Structural Equation Modelling (PLS-SEM). The study confirmed that three factors consisted of 0 (owner manager's ERM knowledge, owner manager's attitude towards ERM), T (complexity) and 0 (firm size) have significant relation with the likelihood of ERM practices. Whereas three factors consisted of T (compatibility), 0 (employees' ERM knowledge level), and E (environmental uncertainty) were supported for the penetration level of ERM practices. This study also revealed that ERM firms outperformed non-ERM firms for both financial and non-financial performance. Communication was found partially mediated between the penetration level of ERM practices and the firm's performance. In conclusion, there are three implications outlined. First, the implication for SME owners, which is the ERM firms' performance, has a higher mean rank compared to non-ERM firms, showing that ERM can be an approach or a tool for SMEs in the decision-making process to enhance productivity and growth. Second, the implication for the government agencies and public sectors, which is, different approaches are needed to encourage non-ERM firms to practice ERM and to increase the penetration level of ERM practices among ERM firms. Third, the implication for academicians, which is, the differences between the ERM firms and non-ERM firm's influential factors made certain the different applications of the conceptual framework for future study.